2018
DOI: 10.1083/jcb.201710078
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulates testosterone synthesis by facilitating cholesterol uptake in Leydig cells

Abstract: High levels of autophagy exist in Leydig cells of the testis, but its physiological function is unknown. Gao et al. now show that autophagy promotes uptake of cholesterol, an essential precursor for testosterone synthesis, by removing the NHERF2 negative regulator of the high-density lipoprotein receptor SR-BI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 50 publications
3
117
0
Order By: Relevance
“…This significant downregulation of beclin1 in HFrD induced MetS group could be linked to the affection of testicular functions as postulated by Tang and Wang [77] who stated that autophagy is considered as an important regulatory mechanism in spermatogenesis and steroid production in testis. This was in line with Gao et al [27] who revealed that autophagy has been reported to be extremely active under normal conditions to promote cholesterol uptake into Leydig cells and hence testosterone production, suggesting that dysfunction of autophagy might be causal in the loss of testosterone production in some patients.…”
Section: Discussionsupporting
confidence: 90%
“…This significant downregulation of beclin1 in HFrD induced MetS group could be linked to the affection of testicular functions as postulated by Tang and Wang [77] who stated that autophagy is considered as an important regulatory mechanism in spermatogenesis and steroid production in testis. This was in line with Gao et al [27] who revealed that autophagy has been reported to be extremely active under normal conditions to promote cholesterol uptake into Leydig cells and hence testosterone production, suggesting that dysfunction of autophagy might be causal in the loss of testosterone production in some patients.…”
Section: Discussionsupporting
confidence: 90%
“…Cells in cluster 6 appear to prepare for steroidogenesis by increasing expression of lysosome/exosome genes, likely employing autophagy to degrade cellular components into steroid building blocks like cholesterol and fats ( Figure 2H; Table S2). Previously, autophagy in Leydig cells was shown to be a rate-limiting step for testosterone synthesis (Gao et al, 2018). Apolipoprotein E (ApoE) is also expressed at this time, indicating that LDL uptake, critical for steroidogenesis, is occurring, in line with genetic evidence in ApoE/LDLR knockout mice (Steinfeld et al, 2018).…”
Section: Single-cell Time-course Analysis Reveals Leydig Cell Differementioning
confidence: 69%
“…The postnatal development process of rat LCs can be artificially divided into three distinct stages: PLCs arising around postnatal day 21 (PND21) (Ye et al, 2017), ILCs around postnatal day 28 (Ge and Hardy, 1998) and most of ILCs eventually mature into ALCs by day 56 (Chen H. et al, 2009). To date, the in vitro culture system of rat LCs has been established (Klinefelter et al, 1987;Wang et al, 2019), and the existence of LCs was also confirmed in human and mice (Lo et al, 2004;Gao et al, 2018). What is noticeable is that few studies about LCs have been carried out in other mammalian animals, except those mentioned above.…”
Section: Introductionmentioning
confidence: 99%